Living (and work) of Peruvian immigrants in Madrid - Pérez Pérez, G.; Veredas Muñoz, S. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The present article is based on the analysis of the information obtained by means of a statistical analysis of a survey conduct among 110 Peruvian immigrants in Madrid. The living conditions of these workers are presented under a series of headings which include the job sectors in which they settle, various aspects of their working conditions and salaries, dwellings, leisure time activities, contact with their country of origin and the strength of their associationism. Previously, a sociodemographic description of the sample in set out based on an analysis of their distribution by age, sex, level of education and other variables of interest such as when and how they came to Spain or their legal situation.